Corruption and Foreign Direct Investment in East Asia and South Asia: An Econometric Study - Quazi, Rahim M. (International Journal of Economics and Financial Issues, 2014)
Many recent FDI studies have focused on the effects of corruption on FDI inflows. Theoretically, corruption can act as either a grabbing hand by raising uncertainty and transaction costs, which should impede FDI, or a helping hand by “greasing” the wheels of commerce in the presence of weak regulatory framework, which should facilitate FDI. This study analyzes the impact of corruption on FDI inflows in East Asia and South Asia – two regions that have recently received huge FDI inflows. Using GLS methodology with 1995-2011 panel data, this study finds that the impact of corruption on FDI is significantly negative and robust, which validates the “grabbing hand” hypothesis. It is also found that, even after accounting for the economic fundamentals, East Asia seems to enjoy a locational advantage in attracting FDI vis-à-vis South Asia. These results further our knowledge of the FDI dynamics, which policymakers should find helpful in devising pro-FDI strategies. Keywords: Foreign direct investment; corruption; East Asia; South Asia JEL Classifications: D73; F21; O53